Room temperature deposition of freestanding BaTiO3 films: temperature-induced irreversible structural and chemical relaxation - Eckstein, Udo; Khansur, Neamul Hayet; Bergler, Michael; Urushihara, Daisuke; Asaka, Toru; Kakimoto, Ken-Ichi; Sadl, Matej; Dragomir, Mirela; Ursic, Hana; de Ligny, Dominique; Webber, Kyle Grant (Journal of Materials Science, 2022)
The room temperature aerosol deposition method is especially promising for the rapid deposition of ceramic thick films, making it interesting for functional components in energy, mobility, and telecommunications applications. Despite this, a number of challenges remain, such as an enhanced electrical conductivity and internal residual stresses in as-deposited films. In this work, a novel technique that integrates a sacrificial water-soluble buffer layer was used to fabricate freestanding ceramic thick films, which allows for direct observation of the film without influence of the substrate or prior thermal treatment. Here, the temperature-dependent chemical and structural relaxation phenomena in freestanding BaTiO3 films were directly investigated by characterizing the thermal expansion properties and temperature-dependent crystal structure as a function of oxygen partial pressure, where a clear nonlinear, hysteretic contraction was observed during heating, which is understood to be influenced by lattice defects. As such, aliovalent doping and atmosphere-dependent annealing experiments were used to demonstrate the influence of local chemical redistribution and oxygen vacancies on the thermal expansion, leading to insight into the origin of the high room temperature conductivity of as-deposited films as well as greater insight into the influence of the induced chemical, structural, and microstructural changes in room temperature deposited functional ceramic thick films.
CRIS-Team WoS Importer:2022-07-29